A rare case of Buschke–Lowenstein tumour of vulva treated with radical radiotherapy. (2nd December 2023) - Chakrabarti, Sutanuka; Kulshrestha, Asmita; Patel, Sonal; Kunikullaya, Suryanarayana; Sharma, Ankit
Abstract: Introduction: Buschke–Lowenstein tumour (BLT) is a rare verrucous lesion often associated with human papillomavirus infection. It is an indolent but locally aggressive lesion usually arising from the genitalia or anorectum, with a potential risk of recurrence and malignant transformation. The first line of management is surgical or laser excision. Topical agents cryotherapy, radiotherapy and chemo-immunomodulators are reserved for residual or recurrent cases and smaller lesions. Methods: A 24-year-old female on antiretroviral therapy presented in our department with a large cauliflower-shaped growth involving the perineum, vulva and lower vagina. A biopsy of the lesion was suggestive of a BLT. Due to the extensive nature of the disease, surgery was deferred. The lesion was treated with definitive external beam radiation therapy (EBRT) using a 6-megavoltage photon beam on a Cobalt-60 unit. Results: Radiotherapy resulted in a significant response without any acute toxicity, following which, topical podophyllin application was advised for the residual perianal lesion. The patient is disease free after 9 months of follow-up. Conclusions: A multidisciplinary approach is important to treat the BLT. Lesions not amenable to surgery or local therapies can be treated with EBRT with reasonable control and acceptable toxicities.